2014
DOI: 10.1016/j.joen.2014.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Bimix Antimicrobial Scaffolds for Regenerative Endodontics

Abstract: Introduction Eliminating and/or inhibiting bacterial growth within the root canal system have been shown to play a key role in the regenerative outcome. The aim of this study was to synthesize and determine in vitro both the antimicrobial effectiveness and cytocompatibility of bi-mix antibiotic-containing polydioxanone (PDS)-based polymer scaffolds. Methods Antibiotic-containing (metronidazole, MET and ciprofloxacin, CIP) polymer solutions (distinct antibiotic weight ratios) were spun into fibers as a potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 31 publications
3
74
0
Order By: Relevance
“…The electrospinning system used in this work consisted of a high-voltage source (ES50P-10W/DAM, Gamma High-Voltage Research Inc., Ormond Beach, FL, USA), a syringe pump (Legato 200, KD Scientific Apparatus, Holliston, MA, USA), and a grounded stainless steel collecting drum connected to a high-speed mechanical stirrer (BDC6015, Caframo, Wiarton, ON, Canada), and was described in detail elsewhere [6, 32, 33]. Processing parameters, including solution concentration, field strength, and flow rate were optimized for the distinct polymer systems to obtain defect-free fibrous membranes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The electrospinning system used in this work consisted of a high-voltage source (ES50P-10W/DAM, Gamma High-Voltage Research Inc., Ormond Beach, FL, USA), a syringe pump (Legato 200, KD Scientific Apparatus, Holliston, MA, USA), and a grounded stainless steel collecting drum connected to a high-speed mechanical stirrer (BDC6015, Caframo, Wiarton, ON, Canada), and was described in detail elsewhere [6, 32, 33]. Processing parameters, including solution concentration, field strength, and flow rate were optimized for the distinct polymer systems to obtain defect-free fibrous membranes.…”
Section: Methodsmentioning
confidence: 99%
“…Porphyromonas gingivalis ( Pg ) (ATCC 33277) and Fusobacterium nucleatum ( Fn ) (ATCC 25586) using agar diffusion assays (n=3/group/bacteria) [33]. Bacteria were cultivated in Brain Heart Infusion (BHI) broth supplemented with 5 g yeast extract/L and 5% v/v vitamin K+ hemin (BHI-YE; Becton, Dickinson and Company) at 37°C in an anaerobic GasPak jar for 24 h [33]. Before testing, the minimum inhibitory concentration (MIC) of ZnO was determined using suspensions of ZnO nanoparticles in PBS at the following concentrations: 100, 250, 500, 1,000, 2,500, 5,000, and 10,000 µg/mL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent findings have shown that antibiotic pastes at clinically advocated concentrations affect the survivability of SCAPs (Ruparel et al, 2012). Thus, as a potentially more cell-friendly disinfection strategy, antibiotic-containing polymer nanofibers capable of acting as a drug delivery system and eliminating root canal infection have been developed (Bottino et al, 2013(Bottino et al, , 2014aPalasuk et al, 2014).…”
Section: Tissue-engineering-based Strategies For Regenerative Endodonmentioning
confidence: 99%
“…1A) may minimize these adverse effects and yet still promote the elimination of bacteria (Bottino et al, 2013(Bottino et al, , 2014aPalasuk et al, 2014). Analysis of high-performance liquid chromatography (HPLC) data, in addition to cell toxicity experiments, has supported the claim of a more biologically friendly strategy when compared with the use of antibiotic pastes, since the quantity of drug(s) released occurs more gradually in a lower concentration than in those used in pastes (Bottino et al, 2013(Bottino et al, , 2014aPalasuk et al, 2014). Meanwhile, lower concentrations of antibiotics demonstrate antimicrobial action against Porphyromonas gingivalis and Enterococcus faecalis biofilms (Bottino et al, 2013).…”
Section: Bioactive Scaffolds For Pulp-dentin Complex Regenerationmentioning
confidence: 99%